2019
DOI: 10.1021/acs.analchem.9b00073
|View full text |Cite
|
Sign up to set email alerts
|

High-Fidelity and Rapid Quantification of miRNA Combining crRNA Programmability and CRISPR/Cas13a trans-Cleavage Activity

Abstract: MicroRNAs (miRNAs) are short noncoding RNAs that post-transcriptionally regulate gene expression. It has been proved that the aberrant expression of miRNAs is related to disease and miRNAs can serve as potential biomarkers for early tumor diagnosis. The clustered regularly interspaced short palindromic repeats (CRISPR)/Cas13a is a recently discovered CRISPR-RNA (crRNA) guided RNA manipulation tool. The recognition of target RNA can morphologically activate the robust nonspecific trans ribonuclease activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
141
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(144 citation statements)
references
References 53 publications
2
141
1
Order By: Relevance
“…The transcleavage activity of the recently reported Cas12a, Cas13a, and Cas14 systems in particular, helps them first bind to the target specifically and then amplify the binding signal by cutting the dual-labeled probe in a nonspecific way (Gootenberg et al, 2017;Chen et al, 2018;Harrington et al, 2018;Qian et al, 2019). New nucleic acid detection technologies for different purposes using the CRISPR/Cas12a and Cas13a systems, such as DETECTR, SHERLOCK and HOLMES etc., have extremely high sensitivities and specificities (single base resolution), and have been developed in combination with other gene amplification methods, including PCR and RPA (Gootenberg et al, 2017Chen et al, 2018;Myhrvold et al, 2018;Santos et al, 2018;Shan et al, 2019). Cas12-based DETECTR and HOLMES need fluorescent detection equipment and therefore are not suitable for fieldbased tests Li et al, 2018;Santos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcleavage activity of the recently reported Cas12a, Cas13a, and Cas14 systems in particular, helps them first bind to the target specifically and then amplify the binding signal by cutting the dual-labeled probe in a nonspecific way (Gootenberg et al, 2017;Chen et al, 2018;Harrington et al, 2018;Qian et al, 2019). New nucleic acid detection technologies for different purposes using the CRISPR/Cas12a and Cas13a systems, such as DETECTR, SHERLOCK and HOLMES etc., have extremely high sensitivities and specificities (single base resolution), and have been developed in combination with other gene amplification methods, including PCR and RPA (Gootenberg et al, 2017Chen et al, 2018;Myhrvold et al, 2018;Santos et al, 2018;Shan et al, 2019). Cas12-based DETECTR and HOLMES need fluorescent detection equipment and therefore are not suitable for fieldbased tests Li et al, 2018;Santos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, Cas13-based system like SHERLOCK, both the target and probe are RNA, which increases the detection costs and reduces the assay's stability. Moreover, the RNA probe can generate false positive results because RNase is ever present and RNA is generally unstable (Gootenberg et al, 2017Myhrvold et al, 2018;Sashital, 2018;Shan et al, 2019). The newly reported naked-eye gene detection platform based on the CRISPR/Cas12a/13a system also needs a centrifugal machine and whole blood samples can interrupt the naked-eye detection (Yuan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…SHERLOCK can achieve a visual readout by combining with lateral flow readout (Gootenberg et al, ). The CRISPR‐Cas13a‐based detection has been successfully applied to detect Zika virus (ZIKV), Dengue virus (DENV), Avian influenza A (H7N9) virus, Ebola virus and other molecules such as miRNA and N1‐methyladenosine (Chen et al, ; Liu et al, ; Myhrvold et al, ; Qin et al, ; Shan, Zhou, Huang, & Xing, ). In this study, the enhanced Cas13a detection by combining RPA, with T7 transcription and the collateral effect of CRISPR‐Cas13a was developed for sensitive, specific, equipment‐free and visual detection of PRRSV targeting the conserved PRRSV M gene.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a trans -cleavage efficiency of at least 10 4 turnovers per target RNA recognized was observed in the case of LbuCas13a, which is a robust enzyme with a high turnover rate(36). Our previous studies have shown that miRNAs at low fM concentrations can be detected using the dual-labeled fluorescent RNA substrates(53). This potent detection ability prompted direct miRNA detection without an amplification step.…”
Section: Resultsmentioning
confidence: 99%